Comparative government and politics : an introduction - Hague, Rod.; Harrop, Martin (Basingstoke : Palgrave Macmillan, 2013)
Long established as the leading text in the field, the new edition has been comprehensively updated and rewritten. Accessible, student-friendly and truly international in its coverage, this edition includes an brand new chapter on voters and increased coverage of rising powers, such as India and Brazil.
Political concepts. -- The state. -- Democracy. -- Authoritarian rule. -- Theoretical approaches. -- Political culture. -- Political communication. -- Political participation. -- Interest groups. -- Political parties. -- Elections. -- Voters. -- Constitutions and law. -- Multilevel governance. -- Legislatures. -- The political executive. -- The bureaucracy. -- The policy process. -- Comparative methods
Previous edition: 2010.
Includes bibliographical references and index.
Keywords: Comparative government; 89.30 political systems: general; 88.70 comparative study of public administration; Politics and Government; Politics and Government; Educational tools (form)